The Influence Of Character Education On Learning Achievement In Economic Subjects Of Grade X Students In SMA Sandikta Bekasi City - Rahman, Chientya Annisa; Winarsih, Sri; Ikhwan, Ikhwan (Soedirman Economics Education Journal, 2024)
This study aims to determine the effect of character education on student achievement in social studies class X at SMA Sandikta Bekasi, West Java Province. The method used in this research is descriptive quantitative. Sampling in this study was used according to the calculation of Isaac and Michael for an error rate of 1%, the trial sample was 120 students from a total population of 180 students. Data collection techniques for the character education variable using a questionnaire or questionnaire method, while for the variable learning outcomes of social studies subjects with the method of documentation in the form of report cards. Testing the analysis prerequisites in this study include the normality test and the linearity test. Data analysis in this research is descriptive analysis to find out the description of variables, simple regression analysis technique is used to test hypotheses. The results of the study note that: there is an influence of character education on the learning achievement of social studies subjects X class of SMA Sandikta Bekasi City. This can be seen from the value of Fcount = 598.259 greater than Ftable= 3.92 (Fcount> Ftable), obtained the equation Y = -0.272 + 0.898X and the magnitude of the influence of character education on the learning achievement of productive subjects by 83.5%.